2005
DOI: 10.1007/s00223-004-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Femoral Diaphysis and Femoral Neck of Female Rats Chronically Exposed to Various Levels of Cadmium

Abstract: The effect of chronic exposure to cadmium (Cd) on the mechanical properties of femoral diaphysis and femoral neck was investigated on a rat model of human exposure. Three-week-old female Wistar rats were exposed to Cd in drinking water at concentrations of 1, 5, 50, or 100 mg/L for 12 months. Biomechanical properties of the femoral diaphysis were evaluated in a three-point bending test and those of the femoral neck in a bending test with vertical loading of the head. Bone mineral content (BMC) and bone mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 31 publications
8
70
1
1
Order By: Relevance
“…Weakening in the bone biomechanical properties, including especially a decrease in the yield and fracture strength, indicates an enhanced bone susceptibility to fracture. Moreover, further study also revealed that cadmium influence cancellous bone and cortical bone mechanical property [5,23]. The rats treated with 1.5mg/kg bw Cd had weakened compression strength and yields strength compared with control which suggested that the L5 and femur became brittle, especially for L5.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Weakening in the bone biomechanical properties, including especially a decrease in the yield and fracture strength, indicates an enhanced bone susceptibility to fracture. Moreover, further study also revealed that cadmium influence cancellous bone and cortical bone mechanical property [5,23]. The rats treated with 1.5mg/kg bw Cd had weakened compression strength and yields strength compared with control which suggested that the L5 and femur became brittle, especially for L5.…”
Section: Discussionmentioning
confidence: 94%
“…Bone is one of the target organs for cadmium toxicity [1]. It has been shown that cadmium could decrease bone mineral density, result in osteoporosis and increase the risk of bone fracture [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurements were taken with an electronic caliper. Based on the geometric characteristics of the tibia, the following parameters were determined as described by Brzóska et al (2005) The content of crude ash and minerals (calcium and phosphorus) in tibial bones was determined after dry mineralization at 650 °C. Ca content was measured by spectrophotometry, and P content was estimated colorimetrically.…”
Section: Methodsmentioning
confidence: 99%